Image clustering technique in oil palm fresh fruit bunch (FFB) growth modeling - Mohd Kassim, Muhamad Saufi; Wan Ismail, Wan Ishak; Ramli, Abdul Rahman; Bejo, Siti Khairunniza (Elsevier (Science Direct), 2014)
Digital images of FFB from anthesis to harvesting stage were acquired and grouped into 25 maturity stages. K-means clustering technique was used to separate the images into three colours clusters that represent three FFB features, Fruitlet, Brown spine and Green spine. The relationship of Hue colour component and FFB maturity stages was established. The FFB was found to grow in three major stages, from week 0 to 5, week 6 to 14 and week 15 to 24. From the relationship a Growth Model was developed and was validated with actual maturity stage. The coefficient of determination, R2 was 0.95.